2019
DOI: 10.1002/jid.3433
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Economic Growth: Some New Empirical Evidence from a Global Sample

Abstract: This paper assesses the impact of corruption control and regulation quality on growth across countries over the period 1996 through 2015. After dealing with the possible endogeneity problem through the dynamic panel data models, our findings are suggestive of the positive effects of corruption control. Thus, our analysis tends to support the ‘sand the wheels' view at the aggregate level as well as for lower and lower–middle‐income countries. Similar results are also obtained for regulation quality. However, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 86 publications
5
22
0
Order By: Relevance
“…Our results indicate a long-term positive relationship between corruption control and economic growth, corroborating the "sand the wheels" hypothesis. Similar results are found in [26], which also uses the corruption control variable, and is lined with the results of [ [32], and also indicate a positive long-term relationship between economic freedom and economic growth, whether in the presence of the variable control over corruption or not.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results indicate a long-term positive relationship between corruption control and economic growth, corroborating the "sand the wheels" hypothesis. Similar results are found in [26], which also uses the corruption control variable, and is lined with the results of [ [32], and also indicate a positive long-term relationship between economic freedom and economic growth, whether in the presence of the variable control over corruption or not.…”
Section: Discussionsupporting
confidence: 90%
“…In [26] dynamic panel data models are estimated for a sample of 103 countries observed from 1996 to 2015. The results suggest positive effects of corruption control on economic growth performance.…”
Section: Corruption and Growthmentioning
confidence: 99%
“…Considering the empirical studies performed so far, and following the theoretical framework for this specific area, this paper is based on the econometric model developed by Thach, Duong, and Oanh [1]. Furthermore, the model used in the research incorporates variables reflecting the quality of governance, such as voice and accountability, government effectiveness, rule of law and control of corruption, relevant from a public choice point of view on corruption and rent-seeking [14,47,48].…”
Section: Methodsmentioning
confidence: 99%
“…The majority of reference literature papers revealed that corruption has a strong negative impact upon economic growth and upon the efficiency of economic activity [10][11][12][13][14]. Corruption negatively impacts private investments, employment rate, and income per capita [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…direct investment), whose consequences are also related to economic growth. Sharma and Mitra (2019) argue that weak state institutions adversely affect certain economic segments and phenomena. Also, it stimulates unfair competition and favours policy-related individuals who expect to take a portion of the social and public property (Nguyen et al, 2018).…”
Section: Hypothesis Developmentmentioning
confidence: 99%